Letrozole cotreatment improves the follicular output rate in high-body-mass-index women with polycystic ovary syndrome undergoing IVF treatment - Liu, Yali; Lin, Jiaying; Shen, Xi; Zhu, Qianqian; Kuang, Yanping (Frontiers in Endocrinology, 2023)
Background: Women who have polycystic ovary syndrome (PCOS) with high body mass index (BMI) typically have an attenuated ovarian response and decreased follicular size, which are linked to unfavourable clinical outcomes following in vitro fertilisation (IVF) therapy. The follicular output rate (FORT), a qualitative indicator of follicular response, seems to be positively linked to the clinical outcomes of IVF. Progestin-primed ovarian stimulation (PPOS) has become an alternative to gonadotropin-releasing hormone (GnRH) analogues to inhibit the premature luteinizing hormone (LH) surge. As letrozole (LE) shows promise in enhancing follicle size and ovarian response, we compared PPOS with and without LE for PCOS in high BMI women with a focus on the FORT and associated clinical and pregnancy outcomes. Methods: A total of 1508 high-BMI (BMI>25) women with PCOS were recruited from January 2017 to September 2022 based on the enrolment criteria. Following propensity-score matching at a 1:1 ratio, 134 women received controlled ovarian stimulation (COS) with medroxyprogesterone acetate (MPA) and human menopausal gonadotropin (hMG) alone, and 134 received the same treatment coadministered with LE. FORT was selected as the primary outcome measure. The number of oocytes retrieved, viable embryos, hMG dosage, duration, oocyte maturity rate, fertilisation rate, and implantation rate were established as secondary outcomes. Results: FORT was substantially elevated in the MPA+hMG+LE group compared with the MPA+hMG group (61% [35%, 86%] vs. 40% [25%, 60%], P < .001). Interestingly, the LE cotreatment group had a considerably lower mature oocyte rate despite having a similar number of mature oocytes and embryos recovered. The average hMG dosages and durations in the trial group were similar to those in the control group. The implantation rate in the study group was nonsignificant higher than that in the control groups (43.15% (107/248) vs. 38.59% (115/298),OR 1.008, 95% CI 0.901-1.127; P > .05). Conclusion: The effect of LE combined with PPOS on FORT is better than the effect of the standard PPOS treatment in women with PCOS and a high BMI, but there is no substantially beneficial impact on pregnancy outcomes or the cycle features of COS, including consumption of hMG.